LAW, MORALITY, JUSTICE, FREEDOM and EQUALITY : The Underlying Concepts - Haswira Nor Mohamad Hashim, author 644510; Anida Mahmood, author 644511 (Kuala Lumpur, MY : McGraw-Hill (Malaysia) Sdn. Bhd., 2009)
This law book contains words by famous jurists and covers the relationship between law and morality, justice, freedom and equality.